Mechanism behind the paper spray chemical ionization phenomenon and the choice of solvent. (25th July 2020) - Kim, Hyungjun; Lee, Hyunwoo; Kum, Daesub; Tae, Heungsik; Cha, Sangwon; Kim, Donghwi; Kim, Sunghwan
Abstract: Paper spray chemical ionization (PSCI) combined with mass spectrometry has been proposed as a sensitive method for the analysis of nonpolar aromatic compounds; however, the mechanism behind PSCI is not well understood. In the present study, the evidence for the occurrence of corona discharge is provided and its mechanism is proposed. Photographs taken with a highly sensitive camera evidently demonstrate the occurrence of corona discharge at the end of the triangular shape tip when a nonpolar solvent such as hexane was used at an applied potential of 6–7 kV. Nevertheless, corona discharge was not observed in the presence of a polar solvent. The occurrence of the corona discharge was attributed to charge accumulation in the dielectric layer generated by the nonpolar solvent on the fibers of the paper tip. Specifically, corona discharge was generated at the tip end when the charge approached a critical threshold. In the presence of a polar solvent, however, the dielectric layer was not generated and, hence, corona discharge was not observed. Based on this information, three nonpolar solvents were selected and their sensitivity for analyzing the phenanthrene and maltene fractions of crude oil was evaluated. Chlorobenzene provided the highest signal abundance; therefore, it was suggested as the optimum solvent for PSCI. Notably, the fundamental understanding of corona discharge in PSCI acquired in this study provides a basis for further improvement of this technique by way of surface modification.